2004
DOI: 10.1080/1462220042000274239
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal nicotine use in postmenopausal women: Does the treatment efficacy differ in women using and not using hormone replacement therapy?

Abstract: This study of postmenopausal female smokers (N = 94) asked: During short-term smoking abstinence, do the beneficial effects of transdermal nicotine replacement therapy (NRT) on acute symptomatology (i.e., withdrawal, cigarette craving, smoking urges, mood, depressive symptoms, motor speed, and reaction time) differ in women who use and do not use hormone replacement therapy (HRT)? Participants were recruited according to HRT and non-HRT use (self-selecting), then randomized within strata to active nicotine or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, self-administration of other drugs of abuse such as alcohol (Freitag and Adesso 1993; Hay et al 1984; Holdstock and de Wit 2000; Nyberg et al 2004; Sutker et al 1987), nicotine (Allen et al 1999, 2004; Snively et al 2000), marijuana (Lex et al 1984), and opioids (e.g., Gear et al 1996) does not vary as consistently with phase of the menstrual cycle in humans as does self administration of stimulants such as cocaine and methamphetamine (see review by Anker and Carroll 2011). Other drug classes may not have been studied extensively enough for a clear pattern of results to emerge, or they are not responsive to hormonal fluctuations over the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, self-administration of other drugs of abuse such as alcohol (Freitag and Adesso 1993; Hay et al 1984; Holdstock and de Wit 2000; Nyberg et al 2004; Sutker et al 1987), nicotine (Allen et al 1999, 2004; Snively et al 2000), marijuana (Lex et al 1984), and opioids (e.g., Gear et al 1996) does not vary as consistently with phase of the menstrual cycle in humans as does self administration of stimulants such as cocaine and methamphetamine (see review by Anker and Carroll 2011). Other drug classes may not have been studied extensively enough for a clear pattern of results to emerge, or they are not responsive to hormonal fluctuations over the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinical work on smoking cessation during specific phases of the menstrual cycle indicated that the follicular phase (low progesterone) may be associated with more favorable outcomes when nicotine replacement therapy is used (Franklin et al 2007; Carpenter et al 2008). In contrast, quit attempts during the follicular phase (vs luteal) result in worse smoking cessation outcomes when behavioral strategies, or when non-nicotine (e.g., buproprion) or no medications are used to treat smoking cessation (Allen et al 1999, 2004, 2008, 2009; Mazure et al 2011). Thus, timing quit attempts to specific phases of the menstrual cycle as a function of the type of abused drug and treatment strategy is potentially important to a successful treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…For example, similar to drug intake, research has been unable to establish a connection between menstrual cycle and self-reported measures of positive affect, intoxication, and craving. Subjective measures were insensitive to menstrual cycle effects following alcohol (Freitag and Adesso, 1993; Hay et al, 1984; Holdstock and de Wit, 2000; Nyberg et al, 2004; Sutker et al, 1987), nicotine (Allen et al, 1999, 2004; Pomerleau et al, 1992, 2000; Snively et al, 2000), marijuana (Lex et al, 1984), and opioid (Gear et al, 1996) administration in women; however, similar to results with cocaine (Evans and Foltin, 2006; Evans et al, 2002; Sofuoglu et al, 1999), women reported decreased positive subjective effects following amphetamine administration during the luteal phase compared to follicular phase of the menstrual cycle (Justice and de Wit, 1999, 2000; White et al, 2002). Overall, these findings indicate a lack of an effect of menstrual cycle phase on behavioral/physiological and subjective measures of alcohol, nicotine, marihuana, and opioid use in humans.…”
Section: Effects Of Progestins On Behavior Maintained By Other Drugs mentioning
confidence: 99%
“…There is some evidence that HT, particularly when combined with antidepressants, can reduce affective symptoms experienced during the menopausal transition (Parry, 2010; Schneider et al, 1997). When examining the effects of HT on mood changes following smoking cessation, Allen and colleagues (2003, 2004) found conflicting results in their two studies (Allen, Hatsukami, Bade, & Center, 2004; Allen, Hatsukami, & Christianson, 2003). In both studies, HT participants were using 0.1 mg estradiol transdermal system and 2.5 mg of Cycrin daily.…”
Section: Menopausal Symptoms and Smoking Cessationmentioning
confidence: 99%